PENGARUH GOOD CORPORATE GOVERNANCE DAN PROFITABILITAS TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015 – 2019 - Equina Noor Shaleha; Sugiarti Sugiarti; Eko Madyo Sutanto (JURNAL ILMIAH EDUNOMIKA, 2023)
The purposive of this study was to analyze The effect of Good Corporate Governance consisting of institusional ownership, board of commissioners, audit committee, audit quality and ROA on tax avoidance. This research focuses on manufacturing companies listed on the Indonesia Stock Exchange in 2015 – 2019. Determination of the number of sample using the purposive sampling metode, so that a sample of 38 manufacturing companies was obtained. The data analysis technique used in this study is the classical assumption test and multiple linear regression analysis using the SPSS 21 program. The results show that the institusional ownership variable has no effect on tax avoidance, the board of commissioner variable has no effect on tax avoidance, the audit committee has a positive effect on tax avoidance. tax avoidance, audit quality has no effect on tax avoidance, ROA has a negative effect on tax avoidance. Keywords: institusional ownership, board of commissioner, audit committee, audit quality and ROA